Cities are for living - Poethig, Richard P. (Quezon City : New Day Publishers, 1972)
Concentrates on growth of Manila. Discusses rural to urban life style changes
Bibliography: p. 37
Keywords: Cities and towns -- Philippines -- Growth; Urban policy -- Philippines; Manila (Philippines) -- Growth